Thunder out of China - White, Theodore H. (William Sloane Associates, 1946)
From the first outbreak of hostilities in northern China in 1937 to the Japanese surrender aboard the U.S.S.Missouri in 1945, this book re-creates the decade of upheaval when China was caught in the grip of revolution and war and torn from its feudal past. The authors Time-Life correspondents during the war years, report firsthand on the rise and fall of the Kuomintang nationalist government and its leader, Chiang Kaishek, who ironically misunderstood his own people as much as the Japanese. At the same time, we see how the Communists won popular support both with more extensive social reforms and with their unrelenting war against Japan. White and Jacoby also shed new light on the actions of "Vinegar Joe" Stilwell (the only American who assessed the Chinese situation accurately) and the diplomacy of Ambassador Patrick J. Hurley, also providing a classic account of the Chinese peasant and his revolution which has since proved to be the recurrent pattern of events in the developing Third World.